Pengaruh Hutang Terhadap Profitabilitas Perusahaan Sektor Consumer Cyclicals yang Terdaftar di BEI Tahun 2020-2022 - Bunga Paska Dewita Oktaviyanti Manurung; Amran Manurung; Magdalena.J Siringoringo (Politeknik Ganesha Medan, 2025)
The ability of a company to generate profits is called profitability. This profit can be used to repay debt and loan interest. Debt itself is divided into two types, namely short-term and long-term debt. Financial ratio analysis analyzes financial statements by comparing one account with another account in the financial statements, the comparison can be between accounts in the balance sheet and profit and loss financial statements. This study aims to determine the effect of short-term debt and long-term debt on profitability. The population in this study were companies in the Consumer Cyclicals sector listed on the IDX for the 2020-2022 period. A total of 139 companies while the sample was determined using purposive sampling method and met the criteria as many as 26 companies. This study uses secondary data obtained through the company's financial statements. The data analysis technique uses the classic assumption test (data normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), multiple linear regression and hypothesis testing. The results of this study can be concluded that short-term debt has a positive effect on profitability and long-term debt has no effect on profitability in Consumer Cyclicals sector companies listed on the Indonesia Stock Exchange in 2020-2022.